The intersection between mindfulness and human rights:The case of Falun Gong and its implications for social work. Issue 1 (2nd January 2016) - Cheung, Maria
ABSTRACT: The author reports on a qualitative study conducted with Falun Gong practitioners in Canada, and explores how a mindful meditative practice can facilitate peaceful resistance to global human rights violations. Falun Gong is a Chinese traditional meditative practice rooted in Buddhist and Daoist philosophies. The Falun Gong experience illuminates a global peace praxis that harmonizes an inward spiritual focus with an outward social action that integrates ethics, morality, and inner transformation in a collective manner through mindful meditative practice. Articulating a few lessons learned from the research, the author discusses how the mindful meditative practice of Falun Gong and practitioners' peaceful resistance can help to expand social work's engagement in the protection of human rights of people of faith on a global scale. The Chinese traditional mindful meditative practice of Falun Gong can help integrate personal, collective, and social transformation to uphold justice and to protect the human rights of all people of faith, which has implications for social work.